2017
DOI: 10.1016/j.physletb.2017.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological constraints on A in p↑p→πX from Lorentz invariance relations

Abstract: We present a new analysis of A N in p ↑ p → π X within the collinear twist-3 factorization formalism. We incorporate recently derived Lorentz invariance relations into our calculation and focus on input from the kinematical twist-3 functions, which are weighted integrals of transverse momentum dependent (TMD) functions. In particular, we use the latest extractions of the Sivers and Collins functions with TMD evolution to compute certain terms in A N . Consequently, we are able to constrain the remaining contri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 99 publications
4
60
0
Order By: Relevance
“…The twist-3 functions describe quark-gluon-quark correlations and trigluon correlations in the polarized proton and have been studied in detail [19][20][21][22][23][24][25][26][27]. Recently, calculations of the twist-3 contribution from parton fragmentation have been carried out and have shown this to be an important mechanism for understanding TSSA measurements [28][29][30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The twist-3 functions describe quark-gluon-quark correlations and trigluon correlations in the polarized proton and have been studied in detail [19][20][21][22][23][24][25][26][27]. Recently, calculations of the twist-3 contribution from parton fragmentation have been carried out and have shown this to be an important mechanism for understanding TSSA measurements [28][29][30].…”
mentioning
confidence: 99%
“…The recent efforts to calculate A N in p ↑ +p and p ↑ +A collisions, accounting for gluon saturation effects [30,[49][50][51] suggested that A N could be A-independent or A −1/3dependent for the different contributions to A N in the region where p T < Q s . However, p T ∼ 2.9 GeV/c in our results is much larger than the saturation scale in the Au nucleus (Q Au s ∼ 0.9 GeV) for the kinematics of this measurement and would lead to no strong A dependence of TSSAs under these models, as calculated in Ref.…”
mentioning
confidence: 99%
“…A series of important work have been done in the past a few decades and the SSAs for the hadron production was completed at leading-order (LO) with respect to the QCD strong coupling constant α s [8][9][10][11][12][13][14] . Recent numerical simulations based on the complete LO result confirmed that the twist-3 approach gives a reasonable description of the SSA data provided by RHIC [19,20].…”
Section: Introductionmentioning
confidence: 83%
“…However, several works in the literature showed later that this cannot be the case [62,63,64]. What is currently understood as the cause of SSAs in pion production is the third term in (2.1) involving twist-3 fragmentation effects [65,66]. The functions we are sensitive to from this mechanism areH(z) and H ⊥(1) 1 (z) [41,67].…”
Section: Ssas Within Collinear Factorizationmentioning
confidence: 91%
“…4 how to approximately recover this relation in the CSS formalism. Both (z) couple to transversity h 1 (x) at larger x values, where the function is currently unconstrained, we can extract h 1 (x) in this region through SSAs in pion production [65,66].…”
Section: Ssas Within Collinear Factorizationmentioning
confidence: 99%